Development and Validation of a Patient Model for Simulating Anaesthetic Uptake - Demgensky Clara; Hennigs Carlotta; Kater Andreas; Bargstädt Björn; Rostalski Philipp (Current Directions in Biomedical Engineering)
Mathematical patient models play a profound role in the managing and understanding of anaesthesia. This article proposes a patient model for simulating anaesthetic uptake, i.e. the storing of anaesthetic gases in the human body, thus extending a well known four compartment model from literature. Real time data is used for the simulation, from which the sevoflurane concentration is extracted. The exhaled concentrations from the model and the data are compared. A literature model is extended with ratios of compartmental perfusion, the introduction of coefficients representing diffusion and the change of the solubility coefficient. The extended and the literature model are applied to five training data sets, with prior optimization of the parameters that have the most impact. Afterwards, both models are validated on five additional data sets. The results of the extended model are mostly better than the results of the literature model. Therefore, the extensions improve the model for the used data, but need to be validated with a larger amount of data.